The Fate of the Fixed Syndesmosis Over Time. (October 2015) - Gennis, Elisabeth; Koenig, Scott; Rodericks, Deirdre; Otlans, Peters; Tornetta, Paul
Background: A prior study demonstrated statistical widening of the syndesmosis within weeks of elective screw removal. However, no information is available as to the radiographic outcomes of screw retention. The aim of this study was to evaluate radiographic syndesmotic widening and talar shift over time in patients treated with syndesmotic screws and to compare screw removal with retention along with other potential risk factors that may have led to tibia-fibula diastasis after weightbearing. Methods: One hundred sixty-six skeletally mature patients with ankle fractures and concomitant syndesmotic injuries were treated with syndesmotic reduction and screw fixation. The syndesmosis was evaluated intraoperatively either by a stress test or direct visualization. If the syndesmosis was incompetent, it was reduced and stabilized with syndesmotic screws to maintain reduction. Anteroposterior, mortise, and lateral radiographs at presentation, postoperatively, and at follow-up after weightbearing were evaluated. We measured the medial clear space (MCS), tibia-fibula overlap (OL), and tibia-fibula clear space (CS). Screws that were retained were graded as loose/broken or intact. Results: The fibula shifted an insignificant amount on postoperative mortise radiographs after elective syndesmotic screw removal at 3 months or more after initial fixation, indicated by a slightly greater CS and lower OL. The MCS did not change from preoperative to postoperative screw removal. There was no change in the radiographic markers from the postoperative to final follow-up images in those whose screws became loose or broken. Likewise, there was no radiographic difference if screws remained intact versus those that were loose or broken. Conclusion: In contradistinction to prior work, we found that only very mild widening (0.5 mm) of the tibia-fibula space occurred after weightbearing following syndesmotic fixation. The removal of syndesmotic screws at 3 months resulted in a slightly lower OL (<1 mm) and greater CS (0.5 mm) on mortise radiographs than screw retention even if the retained screws loosened or broke. This was not associated with any talar subluxation, and these differences were not statistically significant. The mortise remained intact whether the syndesmotic screws were removed, were loosened or broken, or remained solid. Level of Evidence: Level IV, retrospective case series.